A Survey of Medically Important Snails of Gahar Lake in Lorestan Province, Iran - Rouhollah Valipour Nouroozi (Pasteur Institute of Iran, 2014)
Introduction: Some snails play an important role in the transmission of helminthes, mainly trematodes of medical and veterinary importance. There seems to be no information on the freshwater snails of Gahar Lake in Lorestan province of Iran. The present study aimed to identify medically important snails of this lake. Methods: Samples were collected from ten localities around Gahar Lake in April 2015 by hand. The snails were classified according to shells morphology. The data were then analyzed using descriptive statistics. Results: A total of 6 snail species were collected from all localities. Four medically important snail species including: Lymnaea truncatula, Lymnaea peregra, Melanoides tuberculata and Melanopsis spp. were detected. M. tuberculata was seen in all sampling sites. Physa acuta and Melanopsis spp. were observed in five sampling sites. Planorbis intermixtus, L. peregra and L. truncatula were found in four, three and two sampling sites, respectively. Conclusion: Presence of medically important snails in Gahar Lake could be a source of trematode infections for visitors. Therefore control measures, especially biological ones should be applied to the lake.